Pemberdayaan Masyarakat dengan Pelatihan Daun Kelor sebagai Masker Wajah Alami - Rinawati Zailani; Yuni Purnamasari; Indah Istanti; Dwi Wahyuni; Humam Humam; Iyung Cahyono (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
Community empowerment is a very important service activity and must be carried out in an effort to free society from various adversities, disadvantages and underdevelopment. Villages as centers of social and economic life have great potential which has not been fully exploited optimally. The community empowerment program implemented in this village aims to improve the welfare of residents through skills training and business development based on local potential, namely by using Moringa leaves as a natural facial mask. Community service activities carried out include providing education on the importance of Moringa leaves for health, providing scientific insight into the use of Moringa leaves as a natural face mask and providing training on how to make Moringa leaf masks as well as packaging and marketing products to village communities. The results obtained from the community service activities that have been carried out are that the community is enthusiastic about gaining new knowledge and can process the village's potential into useful innovative products.